The effectiveness of audit committee and audit quality towards earnings management of ASEAN public companies - Androjuniko Androjuniko; Tanggor Sihombing (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
The auditing profession has become so important in the general society as well as the business world because of its responsibility in providing assurance in reporting assets such as sustainability and other information, which a variety of stakeholders have their interests in (Arens et al., 2016). The goal of this study is to observe the relationship between the audit committee and audit quality towards earnings management of public companies that operate in the food, beverage, and tobacco industry in the top three GDP countries in ASEAN between 2018 and 2020. The result from various tests in this paper indicates that audit committee independence and audit quality do affect earnings management significantly. On the other hand, audit committee size did not seem to show any significance in influencing earnings management.